2013
DOI: 10.1038/ejhg.2013.106
|View full text |Cite
|
Sign up to set email alerts
|

Non-meiotic chromosome instability in human immature oocytes

Abstract: Aneuploidy has been a major issue in human gametes and is closely related to fertility problems, as it is known to be present in cleavage stage embryos and gestational losses. Pre-meiotic chromosome abnormalities in women have been previously described. The aim of this study is to assess the whole-chromosome complement in immature oocytes to find those abnormalities caused by mitotic instability. For this purpose, a total of 157 oocytes at the germinal vesicle or metaphase I stage, and discarded from IVF cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…A more recent study by the same Spanish group analysed 157 immature oocytes (GV or MI stage) from both IVF patients and IVF donors by metaphase CGH. Fifty-six women of average age 32.5 years included 32 IVF patients (range 25–45 years) and 24 oocyte donors (range 18–33 years) [46]. Overall, 24 oocytes of the 157 showed premeiotic aneuploidy of whole chromosomes (15.3%).…”
Section: Premeiotic Aneuploidymentioning
confidence: 99%
“…A more recent study by the same Spanish group analysed 157 immature oocytes (GV or MI stage) from both IVF patients and IVF donors by metaphase CGH. Fifty-six women of average age 32.5 years included 32 IVF patients (range 25–45 years) and 24 oocyte donors (range 18–33 years) [46]. Overall, 24 oocytes of the 157 showed premeiotic aneuploidy of whole chromosomes (15.3%).…”
Section: Premeiotic Aneuploidymentioning
confidence: 99%
“…This aneuploidy incidence is higher than expected, but the presence of three out of seven women aged between 36 and 37 years should be considered as an influencing factor as well as the fact that not only aneuploidies but also segmental imbalances are considered and informed in the preimplantation genetic screening (PGS) report. Moreover, previous studies reported considerable rates of oocyte aneuploidy even in young women …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies reported considerable rates of oocyte aneuploidy even in young women. 13,14 The aneuploid events affected all of the chromosomes. In the present work, 44.8% of aneuploid blastomeres had at least three or more chromosomes simultaneously altered.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 4 ] Moreover, a high incidence of aneuploidy has also been reported in embryos from in vitro fertilization cycles[ 3 , 5 , 6 ] and in oocytes, even from young donors. [ 4 , 7 , 8 ] The Double Factor-PGT (DF-PGT) allows to transfer not only healthy embryos, free from the monogenic disease, but also embryos with the highest implantation potential according to its cytogenetic characterization. [ 9 , 10 ] This should produce an increase of pregnancy and birth rates in PGT cycles and consequently should reduce the incidence in the populations of genetic illnesses.…”
Section: Introductionmentioning
confidence: 99%